Reciprocal action of pentraxin-3 and CRP in women with polycystic ovary syndrome - (:unkn) unknown (Biolife s.a.s., 2014)
The aim of this study was to investigate the relationship between pentraxin-3 and other biochemical parameters in women with polycystic ovary syndrome (PCOS). We compared 58 women with PCOS to 34 body mass index- and age-matched normally menstruating healthy controls. Women with PCOS had significantly higher DHEA-S, free testosterone, LH and FAI, but lower pentraxin-3 levels when compared to healthy controls (0.86±0.21 and 0.91±0.14 respectively, p=0.014). Levels of CRP and lipoprotein-a were higher in the PCOS group. Overweight PCOS had significantly higher insulin, HOMA-IR, FAI, free testosterone and CRP and statistically significantly lower HDL and SHBG levels when compared to controls. Pentraxin-3 levels of obese and normal weight PCOS were similar. CRP and pentraxin-3 might contribute reciprocally to metabolic events and chronic low-grade inflammation in women with PCOS. Copyright © by BIOLIFE, s.a.s.
Keywords: CRP; Inflammation; Lipoprotein-a; Pentraxin-3; Polycystic ovary syndrome